Serotonin and the CNS New Developments in Pharmacology and Therapeutics - Olivier, Berend (IntechOpen, 2022)
Serotonin is an ancient neurotransmitter system involved in various systems and functions in the body and plays an important role in health and disease. The present volume illustrates the broadness of the involvement of serotonergic activity in many processes, focusing particularly on disorders of the brain, including depression, stress and fear, Alzheimer's disease, aggression, sexual behavior, and neuro-immune disorders. Chapters illustrate techniques and methods used to study the complex role of the serotonergic system in all kinds of processes, present new hypotheses for several brain disorders like sleep and depression, and use mathematical modeling as a tool to advance knowledge of the extremely complex brain and body processes.